1997
DOI: 10.1126/science.275.5304.1295
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecule Force Spectroscopy on Polysaccharides by Atomic Force Microscopy

Abstract: Recent developments in piconewton instrumentation allow the manipulation of single molecules and measurements of intermolecular as well as intramolecular forces. Dextran filaments linked to a gold surface were probed with the atomic force microscope tip by vertical stretching. At low forces the deformation of dextran was found to be dominated by entropic forces and can be described by the Langevin function with a 6 angstrom Kuhn length. At elevated forces the strand elongation was governed by a twist of bond a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
940
1
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,097 publications
(985 citation statements)
references
References 9 publications
41
940
1
3
Order By: Relevance
“…This structural modification was correlated with a change of molecular interactions; while dormant spores showed poor adhesion, germinating spores showed large attractive forces, along with elongation forces that were attributed to the stretching of single cell surface polysaccharides. This interpretation was supported by the finding that fitting the curves with a theoretical model from statistical mechanics yielded parameters similar to those reported for individual amylose and dextran molecules (Rief et al, 1997). It was concluded that the stickiness and flexibility of cell surface polysaccharide chains may promote spore aggregation via macromolecular bridging interactions between opposing cells.…”
Section: Imaging Living Cells and Following Dynamic Processessupporting
confidence: 65%
See 1 more Smart Citation
“…This structural modification was correlated with a change of molecular interactions; while dormant spores showed poor adhesion, germinating spores showed large attractive forces, along with elongation forces that were attributed to the stretching of single cell surface polysaccharides. This interpretation was supported by the finding that fitting the curves with a theoretical model from statistical mechanics yielded parameters similar to those reported for individual amylose and dextran molecules (Rief et al, 1997). It was concluded that the stickiness and flexibility of cell surface polysaccharide chains may promote spore aggregation via macromolecular bridging interactions between opposing cells.…”
Section: Imaging Living Cells and Following Dynamic Processessupporting
confidence: 65%
“…AFM has also proved very useful to probe intramolecular forces associated with single poly- saccharides and proteins, thereby providing quantitative information on their elasticity, on conformational transitions along the chains and on folding/unfolding forces (Rief et al, 1997;Oesterhelt et al, 2000). In a mycological context, AFM was used to pull on macromolecules exposed at the surface of living A. oryzae spores, with the aim of gaining insight into their elasticity ( Figure 6; van der Aa et al, 2001).…”
Section: Imaging Living Cells and Following Dynamic Processesmentioning
confidence: 99%
“…1. As described elsewhere, 14,18,[30][31][32][33] the characteristic plateau at 0.3 nN, which is caused by the chair-boat transition of CMA, can be used to confirm that a single molecule has been stretched. At the end of the plateau in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dextran and I27 protein molecules were chosen for these starting experiments because both of these molecules can be regarded as standard (if not calibrating) samples for single-molecule force spectroscopy, and have been widely studied (see, e.g., (8,13,18,19,(23)(24)(25)(26)(27)(28)(29)(30)). The dissipative properties of both of these molecules have been described elsewhere (8,13).…”
Section: Materials and Materialsmentioning
confidence: 99%